Modification of CDV reactor for carbon nanomaterialns production - Al-Mamun, Abdullah; Al-Saadi, Mohammed A.; Muyibi, Suleyman Aremu; Alam, Md. Zahangir (2010)
Chemical vapour deposition (CVD) reactor is one of the processes commonly used for carbon nanomaterial (CNM) production. This method is economical and provides high yield of good quality CNM. However, improvement of the CVD reactor system was necessary due to its long time requirement to complete each batch of production. A two-stage CVD was designed, locally fabricated and modified to overcome the limitations. Improvements included multistage system, which can be used to perform different processes such as floating catalyst reaction, fixed catalyst process, calcination, reduction and oxidation processes. A cooling system was added to reduce the production time. The system was further modified to increase the adsorption capacity of the products. The time requirement for one batch of run was reduced from 8 hours to 3 hours by improving the system.